Mineralogical and Chemical Records of Icelandic Dust Sources Upon Ny-Ålesund (Svalbard Islands) - Moroni, Beatrice; Arnalds, Olafur; Dagsson-Waldhauserová, Pavla; Crocchianti, Stefano; Vivani, Riccardo; Cappelletti, David (Frontiers in Earth Science, 2018)
This work aims to identify the geochemical and mineralogical markers of Icelandic dust and to differentiate it from the dust of local origin deposited at the Ny-Ålesund station. We characterized representative sediment samples from Iceland and Svalbard and compared them to a set of aerosol samples collected in Ny-Ålesund to check the existence and type of the mineralogical markers. The sediment samples were analyzed by X-ray diffraction (XRD) to detect the mineralogical constrain of the geochemical markers. Both aerosol and sediment samples were examined by scanning electron microscopy coupled with EDS microanalysis (SEM-EDS) and image analysis to detect and to provide a morpho-chemical characterization of the mineralogical markers of dust provenance. Comparison between local and Icelandic sediments reveals the metal oxide particles as the most representative and distinguishing mineralogical/phase markers for Iceland dust sources. In particular, we have considered the magnetite-chromite and the magnetite-ulvospinel associations as marker facies of the tholeiitic magmatic series and the presence of volcanic glass as a further indicator of provenance from Iceland. The morphochemical characteristics of the metal oxide particles in the aerosol samples compared to those of the sediment samples have proved to be a powerful tool to separate Icelandic dust from other sources for dust. In particular, the small size, higher grain boundary complexity and lower Fe/Cr ratios suggest the influence of anthropogenic sources, well in accordance with the results of air mass backward trajectories which reveal a main contribution from industrialized areas in Eurasia. This study shows the reliability of the geochemical characterization of the metal oxide particles for the identification of the source regions of dust. In addition it provides an evidence that Icelandic dust can be transported long range to Svalbard confirming the importance of High Latitude Dust sources.